ANALISIS TINGKAT KEPUASAN WISATAWAN TERHADAP KUALITAS SAPTA PESONA DI KAWASAN WISATA CIHAMPELAS KOTA BANDUNG - Syamsiah, Nurul; Yudi Satriadi; Asep Achmad Muhlisian (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
This study discussed the level of tourist satisfaction with the quality of sapta pesona in the Cihampelas tourist area. The research data was collected by distributing a research questionnaire filled out by tourists in the tourist area of Cihampelas Bandung. Respondents as research samples were taken using accidental sampling techniques. The number of samples in this study was determined using the Lameshow formula, with a confidence level of 95% and a sampling error of 10%. Descriptive analysis is used to analyze data by describing or describing data that has been collected, while to see the level of tourist satisfaction with the Cihampelas Bandung tourist area, Likert scale assistance is used. To make it easier to describe and interpret the variables studied, descriptive statistical processing is carried out. The calculated average value is used as a reference to determine the classification of assessment categories. The results of the study found that sapta pesona has been applied in the tourist area of Cihampelas Bandung with the level of tourist satisfaction with the 7 aspects of sapta pesona is good with a value of 3.92 according to the average assessment of the level of satisfaction. Another finding is that male travelers expressed more good and excellent ratings compared to female travelers.